Social relationships and group dynamics within the supervisory board and their influence on CEO compensation - Fabian Dutschkus; Christian Lukas (Schmalenbach Journal of Business Research (SBUR), 2022)
As financial performance measures are not the sole determinant of chief executive officer (CEO) compensation, researchers have investigated social relationships between the CEO and the supervisory board's (SB's) members to identify other determinants. However, different conclusions have been obtained so far. We argue that disregarding group dynamics in the board's social categorization, which arise because of social relationships between board members, can help explain the mixed evidence. Our results suggest that group dynamics within the SB impact the level of CEO compensation. Surprisingly, more robust social ties between the CEO and SB members can lead to lower CEO compensation. In addition, the effects of social relationships depend on the specific type of social relationships.
Keywords: 650; Executive Compensation; Social Relationships; Supervisory Board Independence